Sufentanil alleviates pre-eclampsia via silencing microRNA-24-3p to target 11β-Hydroxysteroid dehydrogenase type 2. Issue 5 (2nd May 2022) - Yue, Yang; Xu, Fu; Zhang, JiaRong; Zhao, Miao; Zhou, FangFang
ABSTRACT: Pre-eclampsia (PE) is a prevalent pregnancy disease characterized by insufficient trophoblast cell migration (HTR8/SVneo). Consequently, accelerating trophoblast cell proliferation might ameliorate PE. This study assessed the effects and molecular mechanisms of Sufentanil (SUF) on HTR8/SVneo cells proliferation. HTR8/SVneo cells and PE clinical samples were used. Peripheral blood was collected from PE patients' samples, and microRNA (miR)-24-3p and 11β-hydroxysteroid dehydrogenase type 2 (HSD11B2) was analyzed in the blood and cells. HTR8/SVneo cells were treated with varying SUF concentrations or transfected with miR-24-3p mimics/inhibitors, or HSD11B2 elevation vector. CCK-8, colony formation, transwell, and flow cytometry assays were then carried out. Association of miR-24 − 3p with HSD11B2 was investigated. PE animal model was constructed using Wistar rats to verify SUF's role on PE in vivo . According to the results, SUF boosted HTR8/SVneo cell proliferation, and inhibited miR-24-3p to accelerate HSD11B2. MiR-24-3p was increased in PE, while HSD11B2 was inhibited, and miR-24-3p targeted HSD11B2. HSD11B2 reversed miR-24-3p's repression on HTR/SVneo cell advancement. SUF restrained PE's progression in vivo and in vitro via mediating the miR-24-3p/HSD11B2 axis. In conclusion, SUF enhances HSD11B2 via repressing miR-24-3p, thereby suppressing PE's progression. The study provides an insight into the possibility of using SUF as a novel therapeutic target for PE, which acts via combining with miR-24-3p. Graphical abstract: uf0001